Optimizing Family-Friendly Workplaces for a Sustainable Green Lifestyle: Insights from LEGO's Leadership in Denmark - Mahendra, Anggana; Yusriani, Sri (Siber Journal of Advanced Multidisciplinary, 2025)
This study investigates the implementation of family-friendly workplace policies as a means to promote a sustainable green lifestyle at LEGO, Denmark. Using a qualitative research approach, the study explores the insights and experiences of managers at LEGO regarding how organizational policies align with sustainability goals. The research highlights how family-centered initiatives, such as flexible work arrangements and parental leave, positively impact employee well-being and organizational productivity while fostering a culture of environmental responsibility. Findings reveal that family-friendly practices not only improve work-life balance but also encourage employees to adopt sustainable habits, contributing to LEGO’s overarching sustainability vision. The study concludes by offering practical recommendations for organizations aiming to integrate social and ecological responsibilities through employee-centered policies.